The association between age at menarche and anthropometric factors - Saleh Jafarian Dehkordi; Masoud Amiri; Soleiman Kheiri; Masoud Lotfizadeh (Shahrekord University of Medical Sciences, 2024)
Background and aims: The purpose of this study was to investigate the association between age at menarche (AAM) and anthropometric parameters in young female students in Shahrekord, southwest Iran. Methods: A cross-sectional study was conducted in elementary and senior girls' schools in Shahrekord in 2018. The sampling method was multistage cluster sampling. The 633 students were studied out of 4868 students selected before the commencement of the study. The statistical analysis was done with a one-way analysis of variance, Spearman's correlation coefficient, and the Kaplan-Meier estimate. The checklist was used to collect the participants' information. All analyses were conducted using SPSS version 24 (IBM Corp, Armonk, NY, USA). Results: The average AAM of our participants was 13.34±0.95 years. Only 8.5% of the 633 participants had reached menarche before the age of 12. In this study, the association between AAM and height (P<0.001) and weight (P=0.007) were significant, while there was no relationship between AAM and body mass index (P=0.91). Conclusion: This study found that the average AAM was like that found in other studies in Iran and other regions of the world. Furthermore, efficient puberty health education is required for female students, especially those aged 12 years.